Cytological observation of anther structure and genetic investigation of a thermo-sensitive genic male sterile line 373S in Brassica napus L - Yanyan Sun (BMC Plant Biology, 2020)
Abstract Background Photoperiod and/or thermo-sensitive male sterility is an effective pollination control system in crop two-line hybrid breeding. We previously discovered the spontaneous mutation of a partially male sterile plant and developed a thermo-sensitive genic male sterile (TGMS) line 373S in Brassica napus L. The present study characterized this TGMS line through cytological observation, photoperiod/ temperature treatments, and genetic investigation. Results Microscopic observation revealed that the condensed cytoplasm and irregular exine of microspores and the abnormal degradation of tapetum are related to pollen abortion. Different temperature and photoperiod treatments in field and growth cabinet conditions indicated that the fertility alteration of 373S was mainly caused by temperature changes. The effects of photoperiod and interaction between temperature and photoperiod were insignificant. The critical temperature leading to fertility alteration ranged from 10 °C (15 °C/5 °C) to 12 °C (17 °C/7 °C), and the temperature-responding stage was coincident with anther development from pollen mother cell formation to meiosis stages. Genetic analysis indicated that the TGMS trait in 373S was controlled by one pair of genes, with male sterility as the recessive. Multiplex PCR analysis revealed that the cytoplasm of 373S is pol type. Conclusions Our study suggested that the 373S line in B. napus has a novel thermo-sensitive gene Bnms t1 in Pol CMS cytoplasm background, and its fertility alteration is mainly caused by temperature changes. Our results will broaden the TGMS resources and lay the foundation for two-line hybrid breeding in B. napus.